Immunization with inactivated antigens of Neospora caninum induces tolllike receptors 3, 7, 8 and 9 in maternal-fetal interface of infected pregnant heifers - Marin, Maia Solange; Hecker, Yanina Paola; Quintana, Silvina; Leunda, Maria Rosa; Canton, German Jose; Cobo, Eduardo Rubén; Moore, Prando Dadin; Odeon, Anselmo Carlos; Perez, Sandra (2017)
Neospora caninum is an obligate parasite and a major cause of abortion in cattle. Pregnancy failures appear to be associated with weak innate defences on the maternal-fetal interface during infection with N. caninum. Herein, we studied the gene expression of Toll-like receptors (TLRs) in pregnant heifers immunized with different vaccine formulations against N. caninum before mating and then challenged the heifers with live N. caninum on day 70 of gestation. TLR7 and TLR8 expression was upregulated in the placental caruncle of infected-pregnant heifers previously exposed to live N. caninum as immunogen. However, TLR7 and 8 expression in both placenta and caruncle as well as, TLR3 and 9 expression in caruncle were upregulated when heifers were previously immunized with inactivated soluble whole antigens and recombinant NcSAG1, NcHSP20 and NcGRA7 proteins. All dams were carrying viable fetuses when they were culled at day 104 of gestation. Upregulation of TLR7 and IFNγ expression was detected in fetal spleen when their mothers where previously vaccinated with soluble antigens and recombinant NcSAG1, NcHSP20 and NcGRA7 proteins. These studies demonstrate that soluble or recombinant NcSAG1, NcHSP20 and NcGRA7 antigens induce key TLRs expression at the maternal-fetal interface, probably triggering damaging inflammatory cellular immune responses associated with abortion. Previous infection with N. caninum seems to attenuate the innate immune response at the maternal-fetal interface, which could favour pregnancy maintenance and perpetuation of the disease. This finding represents novel information on how N. caninum vaccination and infection modulate TLRs expression at the placenta and fetal spleen, the possible role in the pregnancy outcomes and transplacental transmission of the protozoa.